Pengaruh Pemanfaatan Digital Marketing terhadap Keputusan Pembelian Tanaman Hias di Provinsi Bali - PUTRA, I GUSTI NGURAH DARMA; ANGGRENI, I G.A.A. LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
The Effect of Using Digital Marketing on Purchase Decisions for Ornamental Plants in the Province Bali.  Digital marketing is a marketing technique utilizing digital technology that can adapt to market conditions in the industrial era 4.0. The purpose of the study was to determine the use of the digital marketing mix 4C, to find out the digital marketing platform used by ornamental plants businesses in Bali Province with a qualitative descriptive method, and analyze the relationship between convenience, content, response, security, and trust in product purchasing decisions in digital marketing for the ornamental plants business in Bali Province using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The research sample was divided into 2, namely as many as 10 respondents from ornamental plants businesses in Bali Province that utilized digital marketing and 30 respondents from ornamental plants business respondents. The results of the study show 1) All ornalmental plants businesses have utilized the 4C digital marketing mix, although the minimum currency component can be fulfilled. 2) Most of the ornamental plants  businesses in Bali Province have used the Whatsapp and market place  platforms, then there is only one business each that uses the Youtube platform and personal website. 3) Convenience, content, response, and security have an insignificant relationship, while trust has a significant relationship with product purchase decisions in digital marketing ornamental plants business in Bali Province. Based on these results, it is suggested that ornamental plants entrepreneurs in Bali Province pay more attention to the currency aspect, use more types of digital marketing platforms, and also pay more attention to customer trust to marketing their products.